Radial extracorporeal shock wave therapy in flexor tendon pathology of the hand: A feasibility study - Lutter, Christoph; Schöffl, Volker Rainer; Hotfiel, Thilo; Schmitz, Christoph; Milz, Stefan; Strohm, Peter (Technology and Health Care, 2020)
BACKGROUND: Radial extracorporeal shock wave therapy (rESWT) is an effective and safe non-invasive therapeutic option for various musculoskeletal pathologies. However, data on possible application of radial extracorporeal shock waves (rESWs) on soft tissue components of fingers is still scarce. OBJECTIVE: We now aimed to analyze the feasibility of applying rESWs to human fingers ex vivo. METHODS: Fresh frozen human cadaveric fingers were exposed to rESWs of varying energy density. The penetration of the rESWs into the soft tissue was determined using pressure sensitive Fuji films that were placed underneath the flexor tendons and other soft tissue components at the proximal phalanx. Then, rESWs were applied and activation of the Fuji film was recorded. Software based image analysis was performed on all films treated with rESWT under ultrasound gel. RESULTS: Penetration of the rESWs through the soft tissue was detected in all settings. Increasing energy density of the rESWs resulted in increasing film activation. Image analysis of films used under ultrasound showed a significant difference among the groups. CONCLUSION: The results of this study demonstrate that rESWs can penetrate soft tissues including the flexor tendons of human cadaveric fingers. rESWT should be considered as a valuable potential therapeutic option of different finger pathologies. Further studies focusing on the clinical application of rESWT for finger pathologies are required.
CRIS-Team Scopus Importer:2020-02-04
Keywords: Finger; tendinopathy